1980
DOI: 10.1002/j.1939-4640.1980.tb00018.x
|View full text |Cite
|
Sign up to set email alerts
|

Competition of the Histamine H2 Antagonist Cimetidine for Androgen Binding Sites in Man

Abstract: Gynecomastia and impotence have been described as side‐effects of cimetidine therapy. It has previously been shown that cimetidine possesses antiandrogenic properties and competes for dihydrotestosterone (DHT) binding to the cytosol and nuclear fractions of the rat prostate. Because this interaction may be relevant to the clinical findings in man, the authors analyzed the effects of cimetidine on androgen binding to the human prostate, testis, and serum. Cimetidine competed for DHT binding sites in the human p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1984
1984
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Down-regulation of cyp17 gene observed in male fish can therefore explain the decrease in T levels. Several in vitro observations also indicated that cimetidine could compete with androgens for specific receptor sites (Sultan et al, 1980;Winters et al, 1980). Androgen inhibition has been related to the side effects of cimetidine, e.g., sexual dysfunction and gynecomastia (Garcia Rodriguez and Jick, 1994).…”
Section: Endocrine Disruption Of Adult Zebrafishmentioning
confidence: 97%
See 1 more Smart Citation
“…Down-regulation of cyp17 gene observed in male fish can therefore explain the decrease in T levels. Several in vitro observations also indicated that cimetidine could compete with androgens for specific receptor sites (Sultan et al, 1980;Winters et al, 1980). Androgen inhibition has been related to the side effects of cimetidine, e.g., sexual dysfunction and gynecomastia (Garcia Rodriguez and Jick, 1994).…”
Section: Endocrine Disruption Of Adult Zebrafishmentioning
confidence: 97%
“…Endocrine disrupting potential of cimetidine has also been suggested in several in vitro, and in vivo experimental and clinical studies. Cimetidine competes with androgen for binding to androgen receptors in rat ventral prostate cells and fibroblasts (Sultan et al, 1980;Winters et al, 1980). Cimetidine exposure in rats resulted in decreased serum testosterone levels as well as reduced weight of androgen-dependent tissues, e.g., testes and prostate (Baba et al, 1981;Peden et al, 1981;Anand and Van Thiel, 1982).…”
Section: Introductionmentioning
confidence: 98%